Pengembangan Kekhasan Pendidikan Pondok Pesantren - Moh. Sutomo (FALASIFA : Jurnal Studi Keislaman, 2019)
The oldest educational model in Indonesian islamic school, before the advent of formal education. Islamic boarding schools are representative of the needs of the community itself. Islamic school itself develops along with the development of the surrounding community with local wisdom (local genius). Therefore pesantren develops with their own uniqueness as a form of response to the fulfillment of the needs of Stakeholders.This study aims to reveal the development of the peculiarities of boarding school education, with research subjects Baitul Arqom Balung boarding school Jember. The focus of the research study is a) What is the caregiver's view of education in Islamic boarding schools ?, b) What are the caregiver's views on the development of science and technology, political demands and stakeholders, and c) What activities are carried out in developing the characteristics of the Islamic boarding school ?. The results of this study reveal: 1) That the caregiver's view of education in pesantren is: a) education in the pesantren must be open, b) Education in islamic school for all groups, c) Education dipesantren to think freely and remain spiritually islamic school, 2) view of caregivers Baitul Arqom Balung Jember boarding school on the development of science and technology, social and political changes anddemands stakeholder: that is positive and open by showing: a) Updates in terms of teaching and learning methods in pesantren, including the use of information technology access, b). Updates in terms of content of curriculum content. including teaching general science, especially technology, and c) Renewing pesantren as a center of communitydevelopment. Including equipping students with various scientific disciplines and skills in entering the modern world while still holding on to the spiritual demands, Islamic law and morals. 3) The form of educational activities developed as an effort to develop specialities in the Baitul Arqom Balung Jember Islamic boarding school, among others: a) Muadalah education activities, b) non-formal educational activities, for example: English language development, Arabic language development, scout activities, and activities other units